2014
DOI: 10.1371/journal.pone.0083993
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Receptor Gene Polymorphisms Are Associated with Human Directed Social Behavior in Dogs (Canis familiaris)

Abstract: The oxytocin system has a crucial role in human sociality; several results prove that polymorphisms of the oxytocin receptor gene are related to complex social behaviors in humans. Dogs' parallel evolution with humans and their adaptation to the human environment has made them a useful species to model human social interactions. Previous research indicates that dogs are eligible models for behavioral genetic research, as well. Based on these previous findings, our research investigated associations between hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 54 publications
5
110
0
2
Order By: Relevance
“…The potential role of epigenetic factors contributing to breed differences is also raised by Passalacqua et al (2011) who found that hunting and herding breeds (to which Border Collies belong) looked at a person more than dogs from Mastiff-like and ancient breeds (to which Siberian Huskies belong) at the age of 4 month and when adults, but breed group differences were not seen in 2-month-old puppies. Therefore it is reasonable to assume that markedly different dog breeds (such as Border Collies and Siberian Huskies) Our results (together with the findings of Kis et al, 2014a) suggest that we should be cautious in concluding that oxytocin uniformly facilitate social behaviors in dogs. Similar claims have been made in the human literature (Bartz et al, 2011), however many researchers still report their findings as generalizable to a wider population.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…The potential role of epigenetic factors contributing to breed differences is also raised by Passalacqua et al (2011) who found that hunting and herding breeds (to which Border Collies belong) looked at a person more than dogs from Mastiff-like and ancient breeds (to which Siberian Huskies belong) at the age of 4 month and when adults, but breed group differences were not seen in 2-month-old puppies. Therefore it is reasonable to assume that markedly different dog breeds (such as Border Collies and Siberian Huskies) Our results (together with the findings of Kis et al, 2014a) suggest that we should be cautious in concluding that oxytocin uniformly facilitate social behaviors in dogs. Similar claims have been made in the human literature (Bartz et al, 2011), however many researchers still report their findings as generalizable to a wider population.…”
Section: Discussionmentioning
confidence: 66%
“…In line with these findings, recent research has shown that behavioral responses to intranasal oxytocin treatment can be linked to oxytocin receptor (OXTR) genotype in humans (Feng et al, 2015;Marsh et al, 2012). OXTR polymorphisms, in turn, differentially influence social behavior of both different human populations (Chen et al, 2011) and dog breeds (Kis et al, 2014a). The present study investigates how social behavior is influenced by intranasal oxytocin treatment in two markedly distinct dog breeds (selected for different purposes).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations